The Relationship Between the Implementation of Islamic Values and Patient Loyalty in Inpatient Rooms - Arrum Arrifani Alkhaidar; Nurul Hikmatul Qowi; Masunatul Ubudiyah (Fundamental and Management Nursing Journal)
Introduction: Patient loyalty represents a critical challenge for hospitals and other healthcare organizations. A low level of patient loyalty may negatively affect an institution’s competitiveness and reflect poorly on the quality of healthcare services and workforce performance. In increasingly diverse healthcare settings, incorporating values that align with patients’ beliefs and expectations may play a role in fostering satisfaction and loyalty. This study aims to analyze the relationship between implementing Islamic values in inpatient care and patient loyalty.